2022
DOI: 10.3389/fpsyg.2022.935007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive reappraisal and expression suppression on sadness and the recognition of sad scenes: An event-related potential study

Abstract: Previous studies have found differences in the cognitive and neural mechanisms between cognitive reappraisal and expression suppression in the regulation of various negative emotions and the recognition of regulated stimuli. However, whether these differences are valid for sadness remains unclear. As such, we investigated the effect of cognitive reappraisal and expression suppression on sadness regulation and the recognition of sad scenes adopting event-related potentials (ERPs). Twenty-eight healthy undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…Expressive suppression refers to the act of inhibiting or hiding one’s emotional expressions [ 12 ]. In fact, previous studies have shown that expressive suppression can lead to an increase in negative emotions and physiological arousal [ 12 , 13 ]. PA serves as an alternative to expressive suppression as a means of regulating emotions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expressive suppression refers to the act of inhibiting or hiding one’s emotional expressions [ 12 ]. In fact, previous studies have shown that expressive suppression can lead to an increase in negative emotions and physiological arousal [ 12 , 13 ]. PA serves as an alternative to expressive suppression as a means of regulating emotions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emotion regulation is an umbrella term for awareness, acceptance, and understanding of individual emotions together with abilities and strategies to control impulsive responses (12). Cognitive reappraisal and expressive suppression serve as the most frequently used strategies approached to regulate emotions (13).…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate use of emotion regulation strategies can effectively regulate an individual's mental health status before and after the onset of emotions (25,26). Neurologists have further corroborated the mode of action of different emotion regulation strategies through functional MRI, potential recognition, and more (27,28). Emotion regulation strategies have been applied in neurological disorders treatment, time perception, and psychological support and interventions (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%